Musculoskeletal Imaging for Low Back Pain in Direct Access Physical Therapy Compared to Primary Care: An Observational Study - Michael S Crowell; John S Mason; John H McGinniss (North American Sports Medicine Institute, 2022)
# Background Overutilization of diagnostic imaging is associated with poor outcomes and increased costs. Physical therapists demonstrate the ability to order diagnostic imaging safely and appropriately, and early access to physical therapy reduces unnecessary imaging, lowers healthcare costs, and improves outcomes. # Hypothesis/Purpose The primary purpose of this study was to compare rates of compliance with the National Committee for Quality Assurance -- Healthcare Effectiveness Data and Information Set (HEDIS) recommendations for diagnostic imaging in low back pain between physical therapists and primary care providers in young, athletic patients. # Study Design Retrospective cohort study. # Methods Military Health System Data Repository (MDR) data from January 2019 to May 2020 was reviewed for compliance with the low back pain HEDIS recommendation. The low back pain imaging HEDIS measure identifies the percentage of patients who did not have an imaging study (plain X-ray, MRI, CT Scan) ordered on the first encounter with a diagnosis of low back pain or in the 28 days following that first diagnosis. Chi-square tests compared HEDIS compliance rates, with α = 0.05 set a priori. # Results From January 2019 to May 2020, in patients age 18-24, the MDR database identified 1,845 total visits for LBP identified in the Physical Therapy Clinic and 467 total visits for LBP in the Primary Care Clinic. In the Physical Therapy Clinic, 96.7% of encounters did not have imaging ordered within the first 28 days of onset of symptoms, compared with 82.0% in the Primary Care Clinic (p \< .001). # Conclusions Utilizing data from a national standardized healthcare performance measure, physical therapists practicing in a direct-access setting were significantly more likely than primary care providers to adhere to guidelines for low back pain imaging in young, athletic patients. # Level of Evidence Level 3.